Environment: Revitalizing, restoring, and improving rural areas - Ringler, Claudia; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2019)
Rural areas are critical to the provision of ecosystem services. This chapter explores how economic incentives, innovations, and appropriate institutions can help to address rural environmental degradation and contribute to the health of the planet. Key examples include payments for ecosystem services and removal of environmentally damaging subsidies for electricity, fuels, fertilizer, irrigation water, and other scarce inputs. Innovations such as water harvesting and precision farming can improve agricultural production while conserving scarce resources. Institutional changes that can help motivate and coordinate action for environmental improvement include legal recognition of the rights of rural men, women, and communities to land, water, forests, and fisheries.